Palmatine Derivatives as Potential Antiplatelet Aggregation Agents via Protein Kinase G/Vasodilator-Stimulated Phosphoprotein and Phosphatidylinositol 3‑Kinase/Akt Phosphorylation - Fan, Tianyun; Cheng, Yangyang; Wei, Wei; Zeng, Qingxuan; Guo, Xixi; Guo, Zhihao; Li, Yinghong; Zhao, Liping; Shi, Yulong; Zhang, Xintong; Jiang, Jiandong; Wang, Yanxiang; et al. (Journal of medicinal chemistry, 2022)
Sixty palmatine (PMT) derivatives were synthesized and evaluated for antiplatelet aggregation taking berberine as the lead, and the structure–activity relationship was first systematically described. Among them, compound 2v showed the best potency in reducing adenosine diphosphate (ADP)-induced platelet aggregation in a dose-dependent manner. It greatly suppressed ADP-induced platelet aggregation, activation, and Akt phosphorylation in vitro and ex vivo after oral administration to mice. It also effectively inhibited carrageenan-induced thrombus formation in the mouse tail and lung, as well as reduced the serum P-selectin level. Compound 2v might simultaneously bind to protein kinase G to improve vasodilator-stimulated phosphoprotein phosphorylation and bind to phosphatidylinositol 3-kinase to inhibit Akt phosphorylation, which synergically reduced platelet aggregation, thereby achieving antithrombotic efficacy. Therefore, PMT derivatives constituted a novel family of antiplatelet aggregation agents with the advantage of a good safety profile, worthy of further investigation.